Electronic Health Records and Patient Safety - Tanner, C.; Gans, D.; White, J.; Nath, R.; Pohl, J. (Applied Clinical Informatics, 2015)
Background: The role of electronic health records (EHR) in enhancing patient safety, while substantiated in many studies, is still debated.Objective: This paper examines early EHR adopters in primary care to understand the extent to which EHR implementation is associated with the workflows, policies and practices that promote patient safety, as compared to practices with paper records. Early adoption is defined as those who were using EHR prior to implementation of the Meaningful Use program.Methods: We utilized the Physician Practice Patient Safety Assessment (PPPSA) to compare primary care practices with fully implemented EHR to those utilizing paper records. The PPPSA measures the extent of adoption of patient safety practices in the domains: medication management, handoffs and transition, personnel qualifications and competencies, practice management and culture, and patient communication.Results: Data from 209 primary care practices responding between 2006–2010 were included in the analysis: 117 practices used paper medical records and 92 used an EHR. Results showed that, within all domains, EHR settings showed significantly higher rates of having workflows, policies and practices that promote patient safety than paper record settings. While these results were expected in the area of medication management, EHR use was also associated with adoption of patient safety practices in areas in which the researchers had no a priori expectations of association.Conclusions: Sociotechnical models of EHR use point to complex interactions between technology and other aspects of the environment related to human resources, workflow, policy, culture, among others. This study identifies that among primary care practices in the national PPPSA database, having an EHR was strongly empirically associated with the workflow, policy, communication and cultural practices recommended for safe patient care in ambulatory settings.Citation: Tanner C, Gans D, White J, Nath R, Pohl J. Electronic health records and patient safety – co-occurrence of early EHR implementation with patient safety practices in primary care settings. Appl Clin Inf 2015; 6: 136–147http://dx.doi.org/10.4338/ACI-2014-11-RA-0099
Keywords: Electronic health records and systems; safety culture; organizational change management; work-flows and human interactions; sociotechnical aspects of information technology